Can simulation replace part of clinical time? Two parallel randomised controlled trials - Watson, K.; Wright, Anthony; Morris, N.; McMeeken, J.; Rivett, D.; Blackstock, F.; Jones, A.; Haines, T.; O'Connor, V.; Watson, G.; Peterson, R.; Jull, G. (Wiley, 2012)
Context: Education in simulated learning environments (SLEs) has grown rapidly across health care professions, yet no substantive randomised controlled trial (RCT) has investigated whether SLEs can, in part, substitute for traditional clinical education. Methods: Participants were physiotherapy students (RCT 1, n = 192; RCT 2, n = 178) from six Australian universities undertaking clinical education in an ambulatory care setting with patients with musculoskeletal disorders. A simulated learning programme was developed as a replica for clinical education in musculoskeletal practice to replace 1 week of a 4-week clinical education placement. Two SLE models were designed. Model 1 provided 1 week in the SLE, followed by 3 weeks in clinical immersion; Model 2 offered training in the SLE in parallel with clinical immersion during the first 2 weeks of the 4-week placement. Two single-blind, multicentre RCTs (RCT 1, Model 1; RCT 2, Model 2) were conducted using a non-inferiority design to determine if the clinical competencies of students part-educated in SLEs would be any worse than those of students educated fully in traditional clinical immersion. The RCTs were conducted simultaneously, but independently. Within each RCT, students were stratified on academic score and randomised to either the SLE group or the control (‘Traditional’) group, which undertook 4 weeks of traditional clinical immersion. The primary outcome measure was a blinded assessment of student competency conducted over two clinical examinations at week 4 using the Assessment of Physiotherapy Practice (APP) tool.Results: Students’ achievement of clinical competencies was no worse in the SLE groups than in the Traditional groups in either RCT (Margin [Δ] ≥ 0.4 difference on APP score; RCT 1: 95% CI − 0.07 to 0.17; RCT 2: 95% CI − 0.11 to 0.16). Conclusions: These RCTs provide evidence that clinical education in an SLE can in part (25%) replace clinical time with real patients without compromising students’ attainment of the professional competencies required to practise.